New syllabus primary Mathematics 4 - Dr Foong, Pui Yee; Chang, Suo Hui; Brandon, Oh (Lahore: Oxford university press, 2024)
The New Syllabus Primary Mathematics (NSPM) series is designed with a student-focused approach, ensuring active engagement and helping learners build a strong foundation in Mathematics. Aligned with the Pakistan Single National Curriculum 2020, these textbooks and workbooks provide a comprehensive pathway for mastering key mathematical concepts.